2020
DOI: 10.1186/s13098-020-00570-y
|View full text |Cite
|
Sign up to set email alerts
|

NAFLD as a continuum: from obesity to metabolic syndrome and diabetes

Abstract: Background: The prevalence of non-alcoholic fatty liver disease (NAFLD) has been increasing rapidly. It is nowadays recognized as the most frequent liver disease, affecting a quarter of global population and regularly coexisting with metabolic disorders such as type 2 diabetes, hypertension, obesity, and cardiovascular disease. In a more simplistic view, NAFLD could be defined as an increase in liver fat content, in the absence of secondary cause of steatosis. In fact, the clinical onset of the disease is a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
354
1
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 442 publications
(371 citation statements)
references
References 172 publications
(330 reference statements)
2
354
1
14
Order By: Relevance
“…Due to a continuum from obesity to metabolic syndrome, patients with MAFLD may benefit from early identification of the disease risk and individually targeted treatment ( 13 ). Establishing clinical predictors is necessary for MAFLD diagnosis and risk stratification.…”
Section: Introductionmentioning
confidence: 99%
“…Due to a continuum from obesity to metabolic syndrome, patients with MAFLD may benefit from early identification of the disease risk and individually targeted treatment ( 13 ). Establishing clinical predictors is necessary for MAFLD diagnosis and risk stratification.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, increased numbers of adipose tissue and liver macrophages appears to correlate with progression from simple steatosis to NASH and fibrosis [ 22 , 23 ]. This suggest that adipose tissue dysfunction is important in the generation of steatosis and liver inflammation in patients with NASH [ 21 , 24 ]. Although many factors have been shown to be involved in NAFLD and NASH, how these molecules modulate inflammation and what is the role of the tissue resident liver macrophages (Kupffer cells) and recruited immune cells in driving or inhibiting NASH are yet to be clarified [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, excess DPP4 derived from adipocytes and/or hepatocytes may act as a local mediator of in ammation and adipose/hepatic tissue insulin resistance, thereby forming a link between obesity and the pathogenesis of tpe2 diabetes and metabolic disease. Sodium-glucose transporter 2 inhibitors and glucagon-like peptide 1 receptor agonists have recently shown potential e cacy for the treatment of NAFLD/NASH with diabetes [1,15,16], but are expected to be more effective for NAFLD/NASH in obese diabetic patients. The effects of OMG in decreasing intrahepatic fat accumulation and improving intrahepatic adipose in ammation are expected to be helpful for the treatment of NAFLD/NASH, particularly in non-obese, insulin-resistant, diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Dipeptidyl peptidase 4 (DPP4) is a serine exopeptidase able to inactivate various oligopeptides through the removal of N-terminal dipeptides [1]. The activity of DPP4 seems to be increased in patients with type 2 diabetes, and various in vitro and in vivo studies have demonstrated that this enzyme can interact with proin ammatory pathways [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation